Evaluation of Impact Properties of Fly Ash and S-Glass Reinforced Al-4046 Hybrid Metal Matrix Composites. (2017) - Mallikarjuna, B.E.; Shivanand, H.K.; Reddy, Hemachandra; Hanif Ahamadsab, M.
Abstract: In recent years, Metal Matrix Composites (MMC's) reinforced with Fly Ash particulates have attracted considerable interest due to their inherent good mechanical properties such as tensile strength, compression strength, hardness, wear resistance and impact etc. This research work is concerned about the production of Fly Ash, S-Glass reinforced hybrid Aluminium 4046 Metal Matrix Composites (MMC's) and further to investigate on mechanical properties of the processed composites. In this work, experimental study begins with mixing of Aluminium powder, Fly Ash particulates and S-Glass fibers using a stir casting technique at different weight fraction addition of Fly Ash (2%, 4%, 6%) and S-Glass (3%, 5%, 7%). The test specimens are prepared as per standard to conduct impact test. It has been observed that addition of Fly Ash significantly improves impact strength as compared with that of unreinforced matrix.